The Fraudulent Phenomenon of the Financial Pyramids in the Financial Industry - Ślusarek, Natalia (Journal of Finance and Financial Law, 2022)
The purpose of the article is to present the fraudulent behaviour observable in the financial industry, which is the financial pyramid phenomena, through a detailed description of such occurrences together with the damage and consequences generated. This paper will include a solid piece of knowledge about this behaviour, and will also distinguish the similarities and differences between financial pyramids. Methodology of this paper is the critical analysis of the literature and comparative analysis of selected pyramids according to the criteria to compare and distinguish similarities and differences. Results of the research confirm that the phenomenon of the financial pyramids is very harmful to the financial industry but also to the participants and society as a whole. The losses generate every year are enormous, but on the other hand, there is suffering of the victims as well. To conclude, the financial pyramids are inseparable elements of the financial industry and moreover, they are very dangerous and destructive. The knowledge of the specificity of pyramids increases the safety of financial consumers in the financial market.